Broadening the application of hysteresis in economics: Institutions, policy lock-in, psychology, identity, and ideas - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
This paper argues for broadening the application of hysteresis to institutions, policy lockin, psychology, identity, and economic ideas. Hysteresis is an element of historical processes, and the real world is historical. That explains why hysteresis is pervasive and important. Hysteresis should be a fundamental building block of political economy. Expanding its application in economics is both an opportunity and a challenge. The opportunity is that it provides a means for incorporating political, sociological, and psychological forces which economics tends to neglect. That will enrich economics and can also provide a mutually enriching bridge to other social sciences. The challenge is introducing such concerns raises questions about the character of economics' knowledge claims, which is likely to trigger resistance from economists.
Keywords: B40; E10; E12; E32; P50; 330; Hysteresis; institutions; policy lock-in; psychology; identity; ideas